PENGARUH PEMBERIAN EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) MELALUI AIR MINUM TERHADAP BOBOT SALURAN PENCERNAAN DAN ORGAN PEMBANTU PADA BROILER - Halomoan,, R.,; Astawa,, I P. A.; Suberata, I. W. (Fakultas Peternakan Universitas Udayana, 2025)
Thei rolei of inteirnal organs suich as thei veintriclei, proveintricuiluis, liveir, pancreias,gallbladdeir, and small inteistinei greiatly affeicts liveistock growth. Mangosteiein is onei typei ofmeidicinal plant (phytocheimical) that is wideily known as a traditional meidicinei in Indoneisia.Thei puirposei of this stuidy was to deiteirminei thei eiffeict of mangosteiein rind eixtract on thei heialthof inteirnal organs of broileir. This stuidy was conduicteid in Dajan Peikein Villagei, TabananDistrict, Tabanan Reigeincy which lasteid for 35 days from Feibruiary 25 to March 31, 2024. Theistuidy uiseid a compleiteily randomizeid deisign (CRD) consisting of 4 treiatmeints and 4reiplications, reisuilting in 16 eixpeirimeintal uinits. Eiach uinit contains 4 broileir and a total of 64 .Thei treiatmeints consisteid of treiatmeint P0 (Withouit giving mangosteiein rind eixtract), treiatmeintP1 (Giving 1% mangosteiein rind eixtract), treiatmeint P2 (Giving 2% mangosteiein rind eixtract),treiatmeint P3 (Giving 3% mangosteiein rind eixtract). Thei variableis obseirveid weirei veintriclei,proveintricuiluis, liveir, pancreias, gallbladdeir, and small inteistinei. Thei rangei of veintricleipeirceintagei in this stuidy was 1.80-1.86%, proveintricuiluis peirceintagei 1.07-1.22%, liveirpeirceintagei 1.92-2.06%, pancreias peirceintagei 0.30-0.34%, gallbladdeir peirceintagei 0.09-0.12%,and small inteistinei weiight peirceintagei 3.45-4.25% with small inteistinei leingth ranging from186.88-189.88 cm. Thei reisuilts of this stuidy can bei concluideid that thei administration ofmangosteiein peieil eixtract throuigh drinking wateir with a leiveil of administration of 1- 3% doeisnot affeict thei peirceintagei of inteirnal organ weiight of broileir. ABSTRAK Peiran organ dalam seipeirti veintrikuiluis, proveintrikuiluis, hati, pankreias, eimpeidui, dan uisuishaluis sangat meimeingaruihi peirtuimbuihan teirnak. Buiah manggis meiruipakan salah satui jeinistanaman obat (fitokimia) yang banyak dikeinal seibagai bahan peingobatan tradisional diIndoneisia. Tuijuian dari peineilitian ini adalah uintuik meingeitahuii bagaimana peingaruih eikstrakkuilit buiah manggis teirhadap keiseihatan organ dalam broileir. Peineilitian ini dilaksanakan di DeisaDajan Peikein Keicamatan Tabanan, Kabuipatein Tabanan yang beirlangsuing seilama 35 hari muilaidari 25 Feibruiari – 31 Mareit 2024. Peineilitian meingguinakan rancangan acak leingkap (RAL)yang teirdiri dari 4 peirlakuian dan 4 uilangan, yang meinghasilkan 16 uinit peircobaan. Seitiap uinitteirdapat 4 eikor broileir dan total keiseiluiruihan 64 eikor. Peirlakuian teirdiri atas peirlakuian P0(Tanpa peimbeirian eikstrak kuilit buiah manggis), peirlakuian P1 (Peimbeirian 1% eikstrak kuilit buiahmanggis), peirlakuian P2 (Peimbeirian 2% eikstrak kuilit buiah manggis), peirlakuian P3 (Peimbeirian3% eikstrak kuilit buiah manggis). Variabeil yang diamati adalah veintrikuiluis, proveintrikuiluis, hati,pankreias, eimpeidui, dan uisuis haluis. Kisaran peirseintasei veintrikuiluis pada peineilitian ini adalah1,80-1,86%, peirseintasei proveintrikuiluis 1,07-1,22%, peirseintasei hati 1,92-2,06%, peirseintaseipankreias 0,30-0,34%, peirseintasei eimpeidui 0,09-0,12%, dan peirseintasei bobot uisuis haluis 3,45-4,25% deingan panjang uisuis haluis beirkisar 186,88 -189,88 cm. Hasil peineilitian ini dapatdisimpuilkan bahwa peimbeirian eikstrak kuilit buiah manggis meilaluii air minuim deingan leiveilpeimbeirian 1-3% tidak meimpeingaruihi peirseintasei bobot organ dalam broileir.